Ecological evolution in a semi-arid lake: insights from subfossil diatoms and geochemical indicators in Hulun Lake - Sun, Dunping; Xue, Bin; Yao, Shuchun; Kong, Xiangzhen; Zhang, Can; Du, Chen; Xue, Yufei; Zhang, Yiran (Frontiers in Microbiology, 2025)
Hulun Lake, one of the largest inland lakes in the grassland region of northern China, has undergone distinct ecological changes over the past century due to both natural climatic shifts and human activities. Despite its ecological significance, the long-term drivers behind these changes are still not fully understood, especially the interactions between climate and anthropogenic influences on lake dynamics. To fill this gap, we analyzed sediment core from Hulun Lake, examining subfossil diatom assemblages, geochemical indicators, and sediment characteristics to reconstruct environmental changes and uncover the mechanisms driving them. Our findings reveal a shift from predominantly planktonic to periphytic/benthic diatom communities, associated with changes in nutrient levels and hydrological conditions. Key indicators, such as total phosphorus (TP) and sand content, showed strong correlations with diatom community composition, indicating that nutrient influx and water level fluctuations play crucial roles in lake ecosystem dynamics. Before 1935 AD, Hulun Lake’s ecology was primarily driven by natural climatic variations, supporting eutrophic species in stable, nutrient-rich conditions. From 1935 to 1970 AD, nutrient levels rose gradually, with parts of human impact. However, since 1970 AD, as human activities decrease and the warming and drying trend of rising temperature, reduced precipitation has led to a significant drop in the lake water level and a shrinking water area, which of them have significantly influenced nutrient dynamics and diatom composition. This study underscores the combined effects of climate change and human activities in driving the ecological evolution of Hulun Lake, providing valuable insights for the future conservation and management of similar semi-arid lake ecosystems.